Improving Early Childhood Character through Strengthening the Implementation of Character Education - Rakhmawati; Sirojul Baehaqi; Zainal Abidin (Bulletin of Science Education, 2024)
The purpose of this thesis is to analyze the concept and implementation of character education in early childhood, particularly in preschool education settings. The research approach used is qualitative, with a case study method applied to several early childhood education institutions in Indonesia. Data collection was conducted through observation, in-depth interviews, and documentation of learning activities. The research findings indicate that the success of character education in early childhood is influenced by various factors, including the role of educators, the learning methods applied, and support from the family and school environment. Educators play a central role in introducing character values through positive behavior modeling and approaches tailored to the child’s developmental stage. Play-based and storytelling learning methods have been found to be effective in helping children understand and internalize these values. This journal also identifies challenges in the implementation of character education, including educators’ lack of understanding of basic principles of character education and limited time to fully implement a character curriculum. This highlights the need for better training programs and support for educators to help them understand and develop effective character education strategies. In conclusion, character education in early childhood requires a collaborative approach between schools and families to ensure children receive consistent and sustainable character learning. Thus, this study recommends strengthening partnerships between schools and families, as well as adjusting the curriculum to be more flexible so that character values can be taught optimally.